2006
DOI: 10.1242/dev.02395
|View full text |Cite
|
Sign up to set email alerts
|

Pbx1/Pbx2requirement for distal limb patterning is mediated by the hierarchical control of Hox gene spatial distribution andShhexpression

Abstract: Vertebrate limb development occurs along three cardinal axes -proximodistal, anteroposterior and dorsoventral -that are established via the organization of signaling centers, such as the zone of polarizing activity (ZPA). Distal limb development, in turn, requires a molecular feedback loop between the ZPA expression of sonic hedgehog (Shh) and the apical ectodermal ridge. The TALE homeoprotein Pbx1 has been shown to be essential for proximal limb development. In this study, we first uncover that Pbx1 and Pbx2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
236
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(259 citation statements)
references
References 63 publications
(101 reference statements)
21
236
2
Order By: Relevance
“…Although we cannot exclude that Pbx2 and Pbx3 make isoform-specific contributions to MLL oncogenesis, it is more likely that single Pbx deficiencies are functionally compensated by other members of the Pbx protein family, whereas compound deficiencies reduce total Pbx dosage below a critical functional threshold. In support of this, novel compound-deficient Pbx phenotypes have recently been reported for Pbx1 and Pbx2 in limb development (Capellini et al 2006) despite the fact that Pbx2 deficiency alone results in no phenotype . Our data suggest that reduction of total Pbx (Pbx1, Pbx2, Pbx3) expression substantially below half of wild-type levels is limiting for MLL transformation, thus establishing a critical role for Pbx TALE proteins.…”
Section: Mll-mediated Transformation Is Dependent On Pbx Functionmentioning
confidence: 65%
See 1 more Smart Citation
“…Although we cannot exclude that Pbx2 and Pbx3 make isoform-specific contributions to MLL oncogenesis, it is more likely that single Pbx deficiencies are functionally compensated by other members of the Pbx protein family, whereas compound deficiencies reduce total Pbx dosage below a critical functional threshold. In support of this, novel compound-deficient Pbx phenotypes have recently been reported for Pbx1 and Pbx2 in limb development (Capellini et al 2006) despite the fact that Pbx2 deficiency alone results in no phenotype . Our data suggest that reduction of total Pbx (Pbx1, Pbx2, Pbx3) expression substantially below half of wild-type levels is limiting for MLL transformation, thus establishing a critical role for Pbx TALE proteins.…”
Section: Mll-mediated Transformation Is Dependent On Pbx Functionmentioning
confidence: 65%
“…7B). To investigate whether specific Pbx functions were required for MLL transformation, serial replating assays were performed using FL cells harvested from Pbx3 −/− embryos (E14.5-E18) or bone marrow cells isolated from adult Pbx2 −/− mice Capellini et al 2006). MLL oncoproteins transformed the Pbx-deficient myeloid progenitors as efficiently as wildtype cells ( Supplementary Fig.…”
Section: Mll-mediated Myeloid Transformation Is Codependent On Tale Hmentioning
confidence: 99%
“…3A) (Tarchini et al 2006). Indeed, cell biochemical studies have revealed a direct interaction of Hoxd proteins with the cis-regulatory limb-bud enhancer region of the Shh gene (Capellini et al 2006). In addition, the dynamic expression of the Hand2 transcription factor in the limb field mesenchyme and its posterior restriction during onset of limb-bud development parallels the posterior restriction of polarizing activity.…”
Section: Early Specification and Progressive Expansion/differentiatiomentioning
confidence: 99%
“…Nevertheless, to validate this model we need to analyse compound null mice to identify the interrelationships and overlapping functions of PBC proteins in different developmental pathways of organogenesis. Recently, Capellini and coworkers (Capellini et al, 2006) have shown that decreasing Pbx2 dose in the absence of Pbx1 affects limb development more severely than the loss of Pbx1 alone . Indeed, these authors demonstrated that compound Pbx1/Pbx2 embryos, in addition to their proximal limb defects, exhibit novel and severe distal limb abnormalities, with Pbx1 -/-/Pbx2 +/-embryos displaying loss of distal hindlimb elements, whereas Pbx1 -/-/Pbx2 -/-embryos lack hindlimbs altogether.…”
Section: Loss Of Function Of Pbx Genesmentioning
confidence: 99%